Model based impedance control for haptic interface development using hardware-in-the-loop experimental setup - Wen, Kang (University of Ottawa (Canada), 2004)
Haptic interfacing provides the means through which human operators can interact with virtual environments. A haptic interface contains software simulated virtual environments, controllers and haptic devices. Impedance control is investigated in this thesis from the viewpoint of suitability for haptic interface development. The difference between conventional application of impedance control in robot motion control and its application in haptic interface development is also investigated. A model based impedance control methodology was developed for haptic controller design and proved feasible for defining the interaction between a human operator and a virtual environment. The factors that could have effects to the performance of a haptic interface were also investigated experimentally using parametric studies. The investigation was carried out on a HIL (Hardware-In-the-Loop) experimental setup, which combines the real hardware and mathematically simulated components. This HIL experimental set up can be used as a generic platform for the development and testing haptic interface options before prototypes are built.
Keywords: Engineering, Mechanical.